Assistive Technology Act in special education – A comparative Study between United States of America and Kingdom of Saudi Arabia – - Almulhim, Latifah Ahmed (Journal of Educational and Psychological Sciences, 2021)
Assistive Technology Law is one of the most important laws in the field of special education in developed countries. The laws oblige these countries to provide technical facilities for individuals with disabilities as part of the law on their right to services. This article aimed to compare the assistive technology law in the United States of America and the Kingdom of Saudi Arabia through a set of axes: the organizational structure of assistive technology; the definition of assistive technology; the objective of Assistive Technology Act; provision and maintenance of these technologies; participation of individuals and parents in decisions about assistive technology; the relationship between assistive technology and transition services; funding of assistive technology. In conclusion, this article presented several recommendations related to the development of assistive technologies in the Kingdom of Saudi Arabia.